Pengaruh Model Abad 21 4Cs dalam Meningkatkan Kemampuan Membuat Pertanyaan Tingkat Tinggi Mahasiswa Semester I PGSD FKIP UMSU Materi Gejala Alam TA. 2019/2020 - SARI, SUCI PERWITA; SIREGAR, EKO FEBRI SYAHPUTRA (Jurnal Ilmiah Aquinas, 2020)
This study aims to describe the influence of the 21st Century learning model 4Cs in improving the students’ question making skill in PGSD FKIP UMSU. In addition this study also aims to determine the increase the students’ question making skillfor high thinking question by 21st century model 4Cs in groups and personal. The population were all students of PGSD FKIP UMSU in the first semester of 2019/2020, 302 people. Sampling taken by cluster random sampling class it was obtained samples in the control class amount 43 students and the 44 people in experiment class. The results of this study indicate that the significance obtained from the control class and experimental post test is 0,000, p <0.05, which indicates that there is a significant influence on the control class posttest with the experimental class. In the control class the average obtained was 70.47 while in the experimental class the average obtained was 86.64. This shows that the application of 21st Century learning 4Cs in groups is better than personal.